KUALITAS DAN KUANTITAS PENDIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTsN 8 CIREBON - Muhayah (CV. ADIBA AISHA AMIRA, 2024)
Education is Fundamental pillars for progress nation . Quality good education​ depend on two factor main , i.e quality And quantity educator . Quality educators​ And adequate become precondition For reach objective optimal education . In the era of globalization And development rapid technology , demands​ to quality education the more tall . Educator sued For has 4 qualified competencies​ capable adapt with change And always develop self . On the other hand quantity adequate educators​ is crucial thing​ For ensure access equitable education​ for all child nation And not denied Again that quality education Still low . By Because That institution quality education​ can achieved if institution the supported by qualified educators​ And quantity educators who have good management .​ However Not yet can achieved in a way effective . In in fact Still There is part educator Not yet carry out task And not quite enough he answered in a way professional , proven when learning taking place Still There is participant educate those outside class with reason No enter the teacher. By Because That need exists supervision , evaluation And enhancement competence for quality And quantity educator can increase quality education at MTsN 8 Cirebon. Formulation Problem research (1) indicators What only you can used For measure quality And quantity educator . (2) factors supporter And inhibitor What that's the only thing that influences it quality educator And quantity educator . (3) How possible efforts​ done For increase quality And quantity educator in increase quality education at MTsN 8 Cirebon. Study This use approach qualitative And use method descriptive . Type study This is study field with objective For collect related data about quality And quantity educator in increase quality education at MTsN 8 Cirebon. As for data collection uses method observation, interview And documentation . Deep data analysis study qualitative , done in a way interactive And taking place in a way Keep going continuously until complete with do data reduction, data display and verification. Results study This show that quality And quantity educator in increase quality education with method supervision , evaluation And enhancement competence , p This impact on enhancement quality continuing educator​ continuously can increase quality education at MTsN 8 Cirebon. Although Still There is educators who haven't in a way maximum increase the quality , and exists educators who haven't understand right about use tool technology digitalization as well as means infrastructure yet​ adequate , to be constraint educator For increase competence in increase quality education at MTsN 8 Cirebon